Priority Handling Aggregation Technique (PHAT) for wireless sensor networks - Panagiotou, Christos; Koubias, Stavros; Michail, Harris; Gialelis, John; Tsitsipis, Dimitris; Kritikakou, Angeliki S.; Dima, Sofia Maria (My University, 2012)
Wireless Sensor Networks (WSNs) have limited power capabilities, whereas they serve applications which usually require specific packets, i.e. High Priority Packets (HPP), to be delivered before a deadline. Hence, it is essential to reduce the energy consumption and to have real-time behavior. To achieve this goal we propose a hybrid technique which explores the benefits of data aggregation without data size reduction in combination with prioritized queues. The energy consumption is reduced by appending data from incoming packets with already buffered Low Priority Packets (LPP). The real-time behavior is achieved by directly forwarding the HPP to the next node. Our study explores the impact of the proposed hybrid technique in several all-to-one data flow scenarios with various traffic loads, wait time intervals and percentage of HPP. Our results show gain up to 23,3% in packet loss and 36,6% in energy consumption compared with the direct forwarding of packets. © 2012 IEEE.
Keywords: Aggregation techniques; Data aggregation; Hybrid techniques; Incoming packets; Low priorities; Power capability; Traffic loads; Wireless sensor network (WSNs); Energy utilization; Factory automation; Wireless sensor networks